SOCIAL PROTECTION IN THE CONTEXT OF CLIMATE CHANGE - Tutu R. Eyvazova (Russian Studies in Culture and Society)
The article is devoted to the analysis of current social protection measures applied in the context of climate change. The subject of the analysis is the forms of implementation of social protection.